The shape dependence of chameleon screening - Burrage, Clare; Copeland, Edmund J.; Moss, Adam; Stevenson, James A. (IOPScience, 2018)
Chameleon scalar fields can screen their associated fifth forces from detection by changing their mass with the local density. These models are an archetypal example of a screening mechanism, and have become an important target for both cosmological surveys and terrestrial experiments. In particular there has been much recent interest in searching for chameleon fifth forces in the laboratory. It is known that the chameleon force is less screened around non-spherical sources, but only the field profiles around a few simple shapes are known analytically. In this work we introduce a numerical code that solves for the chameleon field around arbitrary shapes with azimuthal symmetry placed in a spherical vacuum chamber. We find that deviations from spherical symmetry can increase the chameleon acceleration experienced by a test particle, and that the least screened objects are those which minimize some internal dimension. For the shapes considered in this work, keeping the mass, density and background environment fixed, the accelerations due to the source varied by a factor of ~ 3.